Dampak ESG terhadap Model Underwriting Asuransi Umum: Tinjauan Literatur atas Perubahan Regulasi dan Praktik Industri - Pristiwanto Bani; Robidi Robidi (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This article discusses the impact of Environmental, Social, and Governance (ESG) integration on the general insurance underwriting model. This study used a Narrative Literature Review (NLR) to review relevant literature. The NLR review was conducted on scientific publications, industry reports, regulatory documents related to ESG, and general insurance underwriting from 2019 to 2025. The reviewed literature shows that adopting ESG factors in the underwriting process changes risk assessment and creates more sustainable practices in the insurance industry. The analysis results show that companies with higher ESG scores have better underwriting performance and attract more investment while increasing stakeholder trust, including an increasing trend of ESG factor integration into the underwriting process, especially in risk assessment and premium determination. Regulatory changes encourage insurance companies to adopt underwriting practices that consider more environmental and social aspects. This study also identifies challenges in implementation, including the limited standardized ESG data and the need to increase human resource capacity. The implications of this study provide insights for regulators and industry players in developing underwriting policies and strategies that are more responsive to ESG issues, as well as highlighting opportunities for ESG-based insurance product innovation in the future.